Relapsing corticosteroid-dependent polyneuritis. Issue 3 (June 1970) - Matthews, W. B.; Howell, D. A.; Hughes, R. C.
Abstract : Three patients are described with chronic polyneuritis of unknown cause in whom a state of corticosteroid dependence developed. A fatal relapse occurred in one patient. No clinical, electrophysiological, or pathological features were found from which it would have been possible to predict this form of response to treatment.